TOLERANSI DAN KOMPROMI PRO-KONTRA RITUAL TAHLILAN DI MASYARAKAT - Mafruhah, Mafruhah; Atnawi, Atnawi (Fakultas Agama Islam Universitas Islam Madura, 2024)
Tahlilan as the initial event of a person's death, continues for 7 (seven) days, up to 1000 (a thousand days). Tahlilan contains tahlil readings and others to ask for forgiveness for the deceased/deceased to Allah swt. This research is qualitative in a library research accompanied by research in the field of case studies. From this, the researcher tried to peel off this Tahlilan case study because there are two parties, pros and cons. From this, it is hoped that there are two attitudes in the form of tolerance and compromise between parties over the differentiation of attitudes from the ritual. Thus, Muslims understand each other and each party so that they continue to strengthen the unity of Muslims. Tahlilan, there are reasons in the form of nash-nash, both the Qur'an, hadith, ijma', qiyas, ijtihad and maqalah for pro people. Tahlilan, there are reasons for argument in the form of good nash-nash of the Qur'an, ijma' hadith, qiyas, ijtihad, and maqalah for those who are contra. From both sides, with both pros and cons, there is a compromise regarding